From silencing to artivism: the indigenous presence in history museums (Tempo e Argumento, 2024)
This article proposes a reflection on the indigenous presence in history museums in the present time, analyzing especially the exhibitions about indigenous people in Brazil, opened and inserted in the long-term circuit of two museums in the city of Rio de Janeiro: the National Historical Museum and the Historical Museum of the City of Rio de Janeiro, in 2023 and 2022, respectively. The both experiences were jointly curated by indigenous artist Denilson Baniwa. The focus on history museums took as a reference the conception of Ulpiano Bezerra de Meneses, for whom museum objects should be taken as historical documents, and the museum perceived as a constituent part of social life. The article contextualizes the two museums to then analyze aspects of the aforementioned exhibitions, questioning a possible decolonial turn in these experiences, which confront the history of these institutions, as well as the hegemonic narrative of the rest of their long-term exhibitions.
Keywords: history museum; National Historical Museum; Historical Museum of the City of Rio de Janeiro; contemporary indigenous art; Denilson Baniwa